2003
DOI: 10.1080/13506280344000095
|View full text |Cite
|
Sign up to set email alerts
|

The face of fear: Effects of eye gaze and emotion on visual attention

Abstract: We investigated whether a fearful expression enhances the effect of another's gaze in directing the attention of an observer. Participants viewed photographs of faces whose gaze was directed ahead, to the left or to the right. Target letters then appeared unpredictably to the left or right. As expected, targets in the location indicated by gaze were detected more rapidly. In nonanxious volunteers the effects of fearful gaze did not differ from neutral gaze, but fearful expression had a more powerful influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
238
7
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(264 citation statements)
references
References 19 publications
17
238
7
2
Order By: Relevance
“…4), although we did not replicate the specific effects of the different emotional facial expressions on performance (significantly slower responses with angry expressions in high trait anxiety subjects) described by Fox et al (2007). The relationships between trait anxiety and processing of emotional facial expressions with direct gaze warrants further investigation, also in consideration that other authors reported slower responses in anxious individuals to centrally located fearful faces with direct gaze (e.g., Mathews et al 2003). …”
mentioning
confidence: 89%
See 4 more Smart Citations
“…4), although we did not replicate the specific effects of the different emotional facial expressions on performance (significantly slower responses with angry expressions in high trait anxiety subjects) described by Fox et al (2007). The relationships between trait anxiety and processing of emotional facial expressions with direct gaze warrants further investigation, also in consideration that other authors reported slower responses in anxious individuals to centrally located fearful faces with direct gaze (e.g., Mathews et al 2003). …”
mentioning
confidence: 89%
“…Provided that introversion is related to high levels of arousal to social signals (Eysenck 1967), and consistent with evidence on social phobia (Horley et al 2004;Moukheiber et al 2010;Stein et al 2002), we expected that introverts would not show the gaze congruency effect in presence of threatening, and in particular angry, facial stimuli relative to non-threatening (happy and neutral) expressions. Importantly, since previous research showed that the gaze-cueing effect with emotional expressions can interact with trait anxiety (Frischen et al 2007;Fox et al 2007;Mathews et al 2003), in the present experiment we also assessed self-reported levels of trait anxiety to explore the possible relationships between anxiety and intro-/extraversion in modulation of the gaze-cueing effect.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations